(untitled) (Dimensión Antropológica, 2022)
Typhus is an endemic and epidemic disease that had continuous incidence over the Mexican population, even after the XIX century, and remained as one of the main causes of mortality in Mexico City. This research aims to describe the social and medical conditions under which this ailment developed and, especially, its characterization by the medical profession, as well as the means adopted physicians to confront this disease. In addition, this study analyzes the medical explanations and actions adopted, as well as the population’s practices concerning typhus. In this regard, the actions, inasmuch as the way of thinking of doctors involve not only technical aspects and procedures but, also, the cultural, social and economic characteristics of the Mexican society. From this perspective, it is fundamental to consider the sickness, as well as the approaches for its characterization, remediation and prevention, as historical processes.